2011
DOI: 10.17848/rpt193
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of EDA's Partnership Planning Program

Abstract: an annual basis, which would also reflect its status as a-living‖ document that changes with the strategic needs of the community. Awareness of the CEDS should also be increased, possibly though staff presentations, media coverage, and electronic media. 3. EDA can enhance its relationship with EDDs by providing more feedback, by changing the way funding applications are handled at the federal level, and by promoting formal interregional collaborations that allow EDDs to combine forces for projects with other a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Fig. 2 (left) shows the growth of σ during the numerical evolution of the preheating model in (1). It is to be noted that the variance grows explosively during the preheating process, even exceeds the aforementioned bounds σ * = 0.03, and σ * = 0.08, if the smoothing scale is R ≡ 1/k * = 1/aH, see Eq.…”
Section: Primordial Black Holes Formationmentioning
confidence: 96%
See 1 more Smart Citation
“…Fig. 2 (left) shows the growth of σ during the numerical evolution of the preheating model in (1). It is to be noted that the variance grows explosively during the preheating process, even exceeds the aforementioned bounds σ * = 0.03, and σ * = 0.08, if the smoothing scale is R ≡ 1/k * = 1/aH, see Eq.…”
Section: Primordial Black Holes Formationmentioning
confidence: 96%
“…Recent research about the implications of a preheating stage on observable cosmological parameters (CMB, microhalos of dark matter, non-gaussianity) have been reported. In particular PBHs formation has been analysed in different models, it was found that an overproduction of these objects may appear but no conclusive results have been reported [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…This is the impetus behind the federal economic development district (EDD) designations, which are employed to foster economic growth. In fact, EDDs have been shown to play a more dominant role in rural areas (Erickcek et al, 2011). Additionally, grouping counties facing similar challenges, or in the pursuit of similar opportunities, will likely be more successful regarding engaging federal agencies.…”
mentioning
confidence: 99%